Bazaloid karsinom ve genital bölge tutulumu - Ardicoglu, Arslan; Onur, Rahmi; Özercan, İbrahim; Orhan, İrfan (My University, 2000)
: Basaloid squamous carcinoma (BSC) is a different derivative of squamous cell carcinoma that exhibits several other histological, immunohistochemical and ultrastructural features. The primary sites are usually, upper aerodigestive tract, esophagus, lung, anus, cervix, prostate or testes. Abundant mitotic figures and large eosinophilic necrotic areas at the center are the charecteristic histopathological features. Basaloid carcinoma as a scrotal pathology has not been previously reported. In the present case, we report a 73-years old male patient with basaloid carcinoma initially presenting with inguinal area and genital tract involvement and reviewed the case in respect to symptoms, primary site and histopathological findings.
Keywords: Carcinoma; Basal Cell; Scrotum; Carcinoma; Squamous Cell; Basaloid carcinoma; Genitalia; Male